Validity and Reliability of Value Assessment Frameworks for New Cancer Drugs - Bentley, Tanya G.K.; Cohen, Joshua T.; Elkin, Elena B.; Huynh, Julie; Mukherjea, Arnab; Neville, Thanh H.; Mei, Matthew; Copher, Ronda; Knoth, Russell; Popescu, Ioana; Lee, Jackie; Zambrano, Jenelle M.; et al. (Value in health, 2017)
Several organizations have developed frameworks to systematically assess the value of new drugs. These organizations include the American Society of Clinical Oncology (ASCO), the European Society for Medical Oncology (ESMO), the Institute for Clinical and Economic Review (ICER), and the National Comprehensive Cancer Network (NCCN). To understand the extent to which these four tools can facilitate value-based treatment decisions in oncology. In this pilot study, eight panelists conducted value assessments of five advanced lung cancer drugs using the ASCO, ESMO, and ICER frameworks. The panelists received instructions and published clinical data required to complete the assessments. Published NCCN framework scores were abstracted. The Kendall's W coefficient was used to measure convergent validity among the four frameworks. Intraclass correlation coefficients were used to measure inter-rater reliability among the ASCO, ESMO, and ICER frameworks. Sensitivity analyses were conducted. Drugs were ranked similarly by the four frameworks, with Kendall's W of 0.703 (P = 0.006) across all the four frameworks. Pairwise, Kendall's W was the highest for ESMO-ICER (W = 0.974; P = 0.007) and ASCO-NCCN (W = 0.944; P = 0.022) and the lowest for ICER-NCCN (W = 0.647; P = 0.315) and ESMO-NCCN (W = 0.611; P = 0.360). Intraclass correlation coefficients (confidence interval [CI]) for the ASCO, ESMO, and ICER frameworks were 0.786 (95% CI 0.517–0.970), 0.804 (95% CI 0.545–0.973), and 0.281 (95% CI 0.055–0.799), respectively. When scores were rescaled to 0 to 100, the ICER framework provided the narrowest band of scores. The ASCO, ESMO, ICER, and NCCN frameworks demonstrated convergent validity, despite differences in conceptual approaches used. The ASCO inter-rater reliability was high, although potentially at the cost of user burden. The ICER inter-rater reliability was poor, possibly because of its failure to distinguish differential value among the sample of drugs tested. Refinements of all frameworks should continue on the basis of further testing and stakeholder feedback.